Applying multi-theory model of health behaviour change to address implicit biases in public health - Sharma, Manoj (International Journal Of Community Medicine And Public Health, 2017)
A person receiving public health services should not receive a lesser standard of service because of his/her race, gender, age, colour, national origin, disability status, occupation or any other extraneous characteristics. However, sometimes our perception based on these hidden linkages (unconscious, irrepressible, or irrational connotations) may influence our judgements resulting in unfairness which are referred as implicit biases. Such biases can result in poorer quality of care. In public health, where the ultimate motive is to ensure social justice, these implicit biases are thus quite deleterious. The purpose of this article was to examine the implicit biases in public health practice and develop recommendations for education, training and research in this discipline using the application of a novel behavioural theory, multi-theory model (MTM) of health behaviour change. A review of literature in the MEDLINE, CINAHL, Google Scholar, and ERIC databases was performed to prepare this article. The constructs of participatory dialogue in which advantages outweigh disadvantages, behavioural confidence, and changes in physical environment were discussed to initiate behaviour change devoid of implicit biases. The constructs of emotional transformation, practice for change and changes in social environment were discussed to sustain behaviour change devoid of implicit biases. Educational interventions based on MTM need to be adopted by Schools of Public Health in education of public health students and training of public health professionals. Such efforts will reduce implicit biases in the discipline of public health and improve quality of care.